Analisis Penerapan Akuntansi Biaya Lingkungan Pada PT Sinar Sostro - Syalwa Naira Eka Putri; Rizki Aisyah Marpaung (Jurnal Riset Akuntansi, 2024)
Environmental Accounting is an accounting science that has the function of identifying and presenting costs incurred for environmental management purposes. This research aims to determine the application of Environmental Cost Accounting in companies, in terms of identifying and presenting Environmental Costs in companies. This research was conducted at PT. Sinar Sostro. This research is qualitative research that is available, namely information data on PT Sinar Sostro's environmental accounting treatment. The result of this research is that the application of Environmental Cost Accounting in companies in terms of presenting and identifying Environmental Costs has been adjusted to existing Financial Accounting Standards.